Huneeus Madge, Carlos La guerra fría chilena. Gabriel González Videla y la ley maldita. Santiago, Editorial Debate, 2009, 404 páginas. ISBN 978-956-8410-26-1 - Béjares von Chrismar, Sergio (Estudios Avanzados, 2012)
Huneeus Madge, Carlos La guerra fría chilena. Gabriel González Videla y la ley maldita. Santiago, Editorial Debate, 2009, 404 páginas. ISBN 978-956-8410-26-1